2015
DOI: 10.11646/zootaxa.3981.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Four new species of Moneuptychia (Lepidoptera: Satyrinae: Euptychiina) from Brazil

Abstract: This paper describes four new species of Moneuptychia as follows: M. montana Freitas, M. vitellina Freitas & Barbosa, M. pervagata Freitas, Siewert & Mielke and M. wahlbergi Freitas, Barbosa, Siewert & Mielke from south and southeastern Brazil. Details are presented on the morphology of adults of all species, and immature stages for two species, and we discuss the taxonomy and identification of the genus Moneuptychia. The mitochondrial CoxI "barcode" region was used for exploring the utility of this DNA marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Most past studies aiming at elucidating the evolutionary history of Neotropical butterflies have examined the Amazon basin and the tropical Andes, where diversity is highest [ 7 10 ]. By contrast, with the exception of southeastern Brazil [ 11 13 ], much less is known about the butterfly communities of southern South America.…”
Section: Introductionmentioning
confidence: 99%
“…Most past studies aiming at elucidating the evolutionary history of Neotropical butterflies have examined the Amazon basin and the tropical Andes, where diversity is highest [ 7 10 ]. By contrast, with the exception of southeastern Brazil [ 11 13 ], much less is known about the butterfly communities of southern South America.…”
Section: Introductionmentioning
confidence: 99%
“…This is not the only example of an Atlantic Forest genus of Satyrinae whose species richness has increased considerably due to recent studies. Another example is the genus Moneuptychia Forster, 1964 belonging to the subtribe Euptychiina, a predominantly premontane and montane genus whose species also increased from two to eight in the last decade (Freitas 2007 , Freitas et al 2010 , 2015 ), with at least five more undescribed species identified (Freitas et al in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were taken and general aspects of morphology were observed using a Leica®MZ7.5 stereomicroscope equipped with a micrometric scale. Egg size is presented as height and diameter, and head capsule size is the distance between the most external ocelli (as in Freitas 2007 , Freitas et al 2015 ). Terminology for early stages descriptions followed García-Barros & Martín ( 1995 ) for eggs and Stehr (1987) for larvae and pupae.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations